Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai Pada Fakultas Ilmu Komputer Universitas Sriwijaya - Muhammad Deni; Vivin Afini; Marita Pratisila; Kemas Welly Angga Permana (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of the work environment on employeeperformance at the Faculty of Computer Science, Sriwijaya University. This study takes samples using the saturated sample technique because the population is relatively small. Employees of the Faculty of Computer Science, Sriwijaya University consist of Civil Servants (PNS), Non-PNS BLU Employees. The research method is carried out by testing the relationship (quantitative associative) of two variables, namely variable X (Work Environment) and variable Y (Employee Performance) with statistical tests using the Classical Assumption correlation. This study, from a population of 41 people, used a sample of 41 people to fill out a Likert scale questionnaire. The results of the calculation of the Classical Assumption correlation show that the work environment affects employee performance, this can be seen from the r-test with 41 respondents greater than rtable with an error rate of 5%. Based on the results of the calculation of the Coefficient of Determination whichstates that there is a strong correlation between the Work Environment variable and the Performance variable, so it can be seen that rcount is greater than rtable (0.829 > 0.308), meaning Ha is accepted, Ho is rejected. This shows that there is a positive and significant relationship between the Work Environment and Performance of employees of the Faculty of Computer Science, Sriwijaya University.